2007
DOI: 10.1248/jhs.53.170
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Quenching and Immunomodulatory Effect of a Modified Siddha Preparation, Kalpaamruthaa

Abstract: Kalpaamruthaa (KA), a modified indigenous Siddha formulation constitutes Semecarpus anacardium nut milk extract (SA), Phyllanthus emblica and honey. The present study attempt has been to investigate the antioxidant and immunomodulatory activities of KA. Antioxidant activity of KA was determined by using ferric thiocyanate and thiobarbituric acid methods. KA showed higher antioxidant activity when compared with vitamin E (α-tochoperol), a well-known antioxidant. Immunomodulatory activities on humoral and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The IgG mediated formation of antigen-antibody complexes on the surface of mast cells and basophils results in the release of inflammatory mediators of anaphylaxis such as histamine, leukotrienes and prostaglandins (Postma, 1995;Agarwal et al, 1999;Dahanukar et al, 2002;Shanmugam et al, 2007). The effect of UNIM-352 on the degranulation of peritoneal mast cells in sensitized animals was studied and the results showed that UNIM-352 significantly inhibited antigen challenge induced degranulation of mast cells in a dose related manner and also protected the rats against mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IgG mediated formation of antigen-antibody complexes on the surface of mast cells and basophils results in the release of inflammatory mediators of anaphylaxis such as histamine, leukotrienes and prostaglandins (Postma, 1995;Agarwal et al, 1999;Dahanukar et al, 2002;Shanmugam et al, 2007). The effect of UNIM-352 on the degranulation of peritoneal mast cells in sensitized animals was studied and the results showed that UNIM-352 significantly inhibited antigen challenge induced degranulation of mast cells in a dose related manner and also protected the rats against mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the footpad was measured at 24 h after the challenge using a plethysmometer and data acquisition system (Ugo Basile, Italy). The difference in the thickness of the right hind paw and the left hind paw was used as a measure of DTH and the percentage response was evaluated after all treatments ( Shanmugam et al, 2007).…”
Section: Delayed Type Hypersensitivity (Dth) Assaymentioning
confidence: 99%
“…One of the main strategies of herbal treatment is to increase the body's natural resistance to disease/stress causing agents rather than directly neutralizing the agents itself in practice. Plant origin immunomodulatory agents enhanced para immunity, non specific immunomodulation of granulocytes, macrophages, natural killer cells and complement functions [1][2][3][4][5][6] . Immune diseases are big problem for mankind.…”
Section: Introductionmentioning
confidence: 99%